TEXTURE DEPTH DETERMINATION FOR STONE MASTIC ASPHALT (SMA). - Mohamed, A. A; Muniandy, R; hamzah, M O (2004)

(untitled)
The primary road surface characteristics that affect users are safety, noise and riding quality.